Risk and Return : A Case of Selected Automobile Stocks Listed at the National Stock Exchange of India - T., Narayanaswamy; Sheth, Urvi Jitendra; A., Thamotharan; Chowdary, Venu Gopal Rao (Indian Journal of Research in Capital Markets, 2022)
Risk factors, arising due to the dynamic business environment, are expected to have a great influence on the stock market returns. Investors need to collect timely information on these risk factors so that investments can be revisited, and necessary revision should be done to reduce their impact on investment returns. This research attempted to study risk and return of segments of different automobile companies listed on the National Stock Exchange of India. Returns were measured in terms of historical stock returns and reward to risk ratio. Risk was measured as standard deviation and beta. The automobile segments selected for the study were cars, LCVs/HCVs, motorcycles, scooters, and tractors. The share price data of 15 companies were collected for a period from 2009 – 2019. The returns and risk were measured for four-time tenures, namely 1-year tenure, 3-year tenure, 5-year tenure, and 10-year tenure. The basic objective for this was to ascertain the risk and return variation across time and segments. The literature evidence showed that only a very few studies attempted to study the change in risk and returns employing different time tenures. Maruti Suzuki India Ltd. recorded the highest 5-year returns (20%) with the least risk (388%) in the passenger segment. Ashok Leyland Ltd. recorded the highest 5-year returns (18%) with the least total risk (574%) and a positive beta value of 1.11 in the LCVs/HCVs segment. Eicher Motors Ltd. recorded the highest 10-year rate of return (41%) with a total risk of 521% and market risk of 0.77 in the motorcycle segment. Atul Auto Ltd. recorded the highest 10-year returns (30%) with a total risk of 714% and market risk of 0.54 in the scooters and three-wheeler segment. Escorts Ltd. recorded a 5-year return of 41% with a least total risk of 655% and had a 5-year market risk of 1.07 in the tractors segment.